Serum IL-33 level and IL-33 gene polymorphisms in Behcet's disease - Koca, Suleyman Serdar; Kara, Murat; Deniz, Firat; Ozgen, Metin; Demir, Caner Feyzi; Ilhan, Nevin; Isik, Ahmet (Springer Heidelberg, 2015)
Beh double dagger et's disease (BD) is a chronic inflammatory disease. Increased productions of cytokines including interleukin (IL)-1 beta and IL-18 are documented, and IL-1 alpha and beta gene polymorphisms are associated with susceptibility to the disease. IL-33 is a recently discovered member of IL-1 cytokine family. The aim of the study was to detect serum IL-33 level and IL-33 gene polymorphisms in a cohort of BD. Unrelated 117 patients with BD and 149 healthy controls (HC) were enrolled. Serum IL-33 levels were analyzed by enzyme-linked immunosorbent assay method. DNA samples were harvested using an appropriate commercial DNA isolation kit. Four single nucleotide polymorphisms of IL-33 gene (rs7044343, rs1157505, rs11792633 and rs1929992) were genotyped using the appropriate commercial primer/probe sets on real-time PCR. Serum IL-33 level was not significantly different in the BD and HC groups (p > 0.05). However, its level was lower in the active BD patients compared to the inactive ones and HC group (p = 0.044 and p = 0.037, respectively). There was no significant difference in terms of the genotypic and allelic distributions of rs1157505 and rs1929992 polymorphisms (p > 0.05 for all). However, the TT variants of rs7044343 and rs11792633 polymorphisms were very rare, and the T allele frequencies of these polymorphisms were lower, in the BD group compared to the HC group (p < 0.0001 for all). The rs7044343 and rs11792633 variants of IL-33 gene are associated with the decreased risk of BD in our cohort. Therefore, it may be concluded that IL-33 acts a protective role on the pathogenesis of BD.
Keywords: Behcet's disease; IL-33; Polymorphisms